Report on the 19th International Scientific Conference in the series “Humanistic Ecology” entitled Environmental Philosophy and Ethics in the Face of the Ecological Crisis (Warsaw, 18–20 September 2025) - Klimski, Marcin (Studia Ecologiae et Bioethicae, 2026)
The International Scientific Conference in the “Humanistic Ecology” series, entitled Environmental Philosophy and Environmental Ethics in the Face of the Ecological Crisis, was held in Warsaw on 18–20 August 2025. Co-organized by Studia Ecologiae et Bioethicae (SEeB), it brought together scholars representing a range of disciplines, including environmental philosophy, ethics, theology, education, law, and the social sciences. Over three days, participants presented a broad spectrum of research and analyses addressing the contemporary ecological crisis, the human–nature relationship, sustainable development, and the ethical consequences of ongoing environmental change. In addition to plenary sessions, the programme included parallel thematic sessions that enabled in-depth discussion of climate change, biodiversity, environmental responsibility, and the axiological foundations of responses to ecological challenges. The conference also strengthened international academic cooperation within the “Humanistic Ecology” network. An important outcome was the support of publication pathways in SEeB: selected papers have already been published or made available as Online First articles, while further texts remain under editorial development.